Natural products targeting autophagy and apoptosis in NSCLC: a novel therapeutic strategy - Qin, Peiyi; Li, Qingchen; Zu, Qi; Dong, Ruxue; Qi, Yuanfu (Frontiers in Oncology, 2024)
Lung cancer is the leading cause of cancer-related mortality worldwide, with non-small cell lung cancer (NSCLC) being the predominant type. The roles of autophagy and apoptosis in NSCLC present a dual and intricate nature. Additionally, autophagy and apoptosis interconnect through diverse crosstalk molecules. Owing to their multitargeting nature, safety, and efficacy, natural products have emerged as principal sources for NSCLC therapeutic candidates. This review begins with an exploration of the mechanisms of autophagy and apoptosis, proceeds to examine the crosstalk molecules between these processes, and outlines their implications and interactions in NSCLC. Finally, the paper reviews natural products that have been intensively studied against NSCLC targeting autophagy and apoptosis, and summarizes in detail the four most retrieved representative drugs. This paper clarifies good therapeutic effects of natural products in NSCLC by targeting autophagy and apoptosis and aims to promote greater consideration by researchers of natural products as candidates for anti-NSCLC drug discovery.In the physiological state, the cell maintains a very low level of basal autophagy. At this time, there is sufficient intracellular energy, Mammalian target of rapamycin complex 1 (mTORC1) is in an activated state and phosphorylates Autophagy Related Protein (ATG) 13, thus inhibiting cellular autophagy. Under stress such as hypoxia, the reduction in ATP levels activates AMP-activated protein kinase (AMPK), which phosphorylates tuberous sclerosis complex 2 (TSC2) to inhibit mTORC1 activity (32,33).When the cell is under nutrient and energy deficiency, protein accumulation, and stress state, the activity of mTORC1 is inhibited, the phosphorylation level of ATG13 decreases, and the dephosphorylated ATG13 forms a complex with Unc-51-like kinase 1 (ULK1) and interacts with FAK family kinase-interacting protein of 200 kDa (FIP200) to produce the ATG13-ULK1-FIP200 complex, and induces downstream autophagosome nucleation and elongation (34)(35)(36). The nucleation process is closely related to the Vacuolar Protein Sorting 34 (Vps34) -Beclin-1 complex, which also contains Vacuolar Protein Sorting 15 (Vps15), and together